Tópicos Obrigatórios em Pediatria: diagnóstico por pediatras do Transtorno do Espectro do Autismo (TEA): um papel crucial na detecção precoce e intervenção adequada - Danilo de Assis Pereira (Residência Pediátrica)
This article aims to address the essential aspects of the Standardization Proposal for the Diagnosis, Investigation, and Treatment of Autism Spectrum Disorder (ASD), providing valuable guidance for pediatric residents.